Repurposing Nano Curcumin: Unveiling its Therapeutic Potential in Diabetic Nephropathy - Sharma, Rarchita; Mali, Yogesh; Agrawal, Yogeeta. O.; Agnihotri, Vinit V.; Goyal, Sameer N. (Current Drug Targets, 2025)
Currently, Diabetic Nephropathy (DN) stands as the predominant global cause of end-stage renal disease. Many scientists believe that diabetes will eventually spread to pandemic levels due to the rising prevalence of the disease. While the primary factor leading to diabetic nephropathy is vascular dysfunction induced by hyperglycemia, several other pathological elements, such as fibrosis, inflammation, and oxidative stress, also contribute to the progression of the disease. The primary targets of current DN therapy approaches are the underlying abnormalities of hypertension and glucose. With several targets and fewer side effects, curcumin is a commonly utilized antioxidant in DN. The present study emphasizes the critical role of oxidative stress and inflammation in the development of diabetic nephropathy. It reveals how these factors induce damage in key kidney cell types, highlighting their potential as therapeutic targets for this disease. In addition, by concentrating on Nrf2, SIRT1, HMGB1, NF-κB, and NLRP3 of curcumin, has strong anti-inflammatory and antioxidant characteristics. This review describes the role of curcumin in the therapeutic application of diabetic nephropathy. In this attempt, we tried to elaborate on the bench-to-bedside aspects of curcumin in DN, including clinical and preclinical investigations. The rationales of curcumin’s mechanisms in alleviating symptoms of the DN were discussed. Curcumin could serve as the potential therapeutic agent for the patient seeking to recover from DN.
Keywords: Diabetic nephropathy; diabetes mellitus